On a Taxonomy of Extension Practices [in Historical Perspective] - Zavaro Pérez, Carlos A. (2020)
This paper analyzes some modalities of the extensionist practice, emphasizing the particularities and the relevance of the economic and socio-political context in which this practice occurs. Categories, such as paradigm, format, device, and tool, are used and discussed in this hierarchical taxonomic system that is defined by two paradigms (transferencism paradigm and problematization paradigm), under which the different recognized formats can be grouped: informative format, awareness-raising format, professionalizing format, classroom intervention format, community intervention format (technocratic-solidarity or critical modalities), and a format that integrates the academic practices, finding in some of them the possibility of belonging to both paradigms and the ductility of some tools recognized as mediation of the practice.